The impact of environmental, social and governance index on firm value: Evidence from Malaysia - Muhammad, Sadiq; Jaspal, S. J. S. *; Muhammad, Raza; Shafi, M. (EconJournals, 2020)
In this study we investigates the relationship of environmental, social and governance (ESG) practices and the consequences related to their disclosure on the firm's value. Our data is extracted from the final accounts of 122 firms listed on Bursa Malaysia over the period 2011 to 2019 with 1098 observations. We used three instrumental variables in this study in order to find the endogeneity of ESG performance namely, the existence of a CSR committee on the Board of directors, dispersion of forecasted earnings and finally the ownership concentration of the firm. We used three first stage regression models related to ESG disclosure and the interaction between the strength, concern, and disclosure of ESG. Besides that, we also use the second stage regression to investigate the insider effects of ESG activities and ESG disclosure. Our results are consistent with the approach that indicate that ESG strength increases firm value whereas ESG disclosure and ESG concern decreases the firm value. Most importantly, this study finds that ESG disclosures can play the role by which a firm can reduce the negative effect of weakness and improve the positive effect of strength.